Connecting the dots: DNA barcoding and lectotype designation shedding light on Labrundinia longipalpis (Goetghebuer, 1921), an intriguing non-biting midge (Chironomidae, Tanypodinae) - Silva, Fabio Laurindo Da (Zootaxa, 2023)
Accurate taxonomic classification is deemed paramount for gaining an understanding of the diversity and distribution of insect species. In this study, an essential stride was made towards advancing the taxonomy of the non-biting midge Labrundinia longipalpis (Chironomidae, Tanypodinae), which serves as the type species of the genus. The distribution of L. longipalpis is particularly intriguing as it contrasts with the predominantly tropical distribution of the genus, with this species being found across the Holarctic region. The main goal of this investigation was to designate a lectotype and several paralectotypes, which was achieved through a comprehensive reexamination of the original material, alongside additional specimens obtained from the type-locality in Flanders. Furthermore, the distribution of L. longipalpis across Europe and North America was examined, and the proposed synonymization of L. maculata with the latter was challenged using the analysis of molecular data. Through the comparison of DNA barcodes, it was revealed that the North American population of L. longipalpis clustered together with the European population, which alludes to a considerable level of genetic similarity between these two populations. These results provide valuable insights into the behavior, ecological dynamics and biogeography of L. longipalpis, while also raising interesting questions about colonization and distribution patterns attributed to its adaptability and potential for long-distance dispersal.